Etiology of ascites in adults living in the Hills of Himachal Pradesh, India: A hospital-based study - Bhupinder Kumar; Brij Sharma; Sujeet Raina; Neetu Sharma; Dalip Gupta; Kavita Mardi (Wolters Kluwer Medknow Publications, 2016)
Aim: Ascites is one of the major complications of liver cirrhosis. In addition, ascites can develop because of peritoneal tuberculosis, malignancy, cardiac, and renal disorders. The purpose of this study was to evaluate epidemiological data on the etiological profile of ascites in adults in a tertiary care hospital in the Northern hilly state of the Western Himalayas. Materials and Methods: A 1-year hospital-based cross section observational study was conducted in the Department of Medicine and Gastroenterology in a tertiary care center of Himachal Pradesh, located in the Northern India. In all 168 patients who were diagnosed as ascites on the basis of history, physical examination, ultrasonography, and of age >18 years were included in the study. Detail history examination and investigation were carried in each case as per protocol. Results: Cirrhosis of liver was the leading cause of ascites in our study (60.7%), tuberculosis was the second most common cause of ascites (13%), malignancy and cardiac disorders were the third (7.7%) most common causes for ascites. Alcohol was the leading cause of cirrhosis in 75 patients (73.5%). Conclusion: The study identified cirrhosis of liver as the leading cause of ascites and alcoholism as the most common cause of cirrhosis. The measures on taking care of preventable risk factors are desired.